A STUDY OF THE MAIN CHARACTER’S RESPONSIBILITY DEPICTED IN STEVEN PIZIKS NOVEL “EXORCIST:THE BEGINING” - Ratna Sari Dewi; Rezky Khoirina Tarihoran (PHILOLOGY Journal of English Language and Literature, 2022)
This research discusses the responsibility depicted in Steven Piziks’ Exorcist: The Beginning. This responsibility is described trough the role of one of the main characters, chuma, pertaining to this close relation to his boss, Merrin.The analysis is divide into two sections i.e. responsibility for duty and responsibility for friendship. The former is related with the discussion on how Chuma works with Merrin, and whatever he does that gradually gives rise into the beginning of their friendship. The former describes more about the enternal friendship between Chuma and Merrin. This results indicate that the responsibility in a working circumstance could bring about an1 everlasting friendship between a boss and his worker. Then, Chuma as Merrin subordinate and close friend fights to defend Merrin from a Turkana soldier’s attack that it finally takes Chuma's life. This description, therefore, shows a friend in need is a friend indeed.